2021
DOI: 10.1002/aic.17510
|View full text |Cite
|
Sign up to set email alerts
|

Method to concurrently measure local gas and solid holdups visually with higher precision in circulating fluidized bed

Abstract: Simultaneous and visual measurements of local gas and solid phase holdups with high-precision in a gas-liquid-solid circulating fluidized bed is of great importance for the design and scale-up of such a reactor. However, such measuring techniques are still limited due to the difficulty of discrete phase identification of gas bubble and solid particle phases in the complex three-phase flow. Immersed telecentric camera method developed based on the digital image processing is such a measuring technique, but its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…There is a need to develop a new recognition program to improve the efficiency of bubble recognition. Of course, its precision also needs to be further improved, and some results have been achieved …”
Section: Discussionmentioning
confidence: 99%
“…There is a need to develop a new recognition program to improve the efficiency of bubble recognition. Of course, its precision also needs to be further improved, and some results have been achieved …”
Section: Discussionmentioning
confidence: 99%
“…In the gas-liquid-solid three-phase fluidized bed, solid clusters and bubble clusters are generated due to the nonuniform distribution of the three phases [10,11]. Clusters can lead to a decrease in contact efficiency or mass transfer, so detecting the cluster distribution is particularly important for the reaction process [12].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of multiphase flow measurement technology, the image-based method, optical fiber probe, conductivity probe, tomographic methods, etc. can now be utilized to acquire the bubble size distribution and the dispersed phase holdup distribution, which provides favorable conditions for understanding the local hydrodynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method encounters some challenges, such as particle identification within the depth of field, dim bubble extraction, and counting overlapping particles. 13 Therefore, it is still a difficult task to count the BSD in gas−liquid−solid three-phase systems due to the complexity of the fluid motion and various interactions among phases. 31 Lee et al 11 utilized PIV to investigate the BSD in a slurry bubble column and found that small bubbles had to be considered when evaluating the bimodal bubble size distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation